Review on High-Temperature Resistance Performance of Slag-Fly Ash-Metakaolin Geopolymer Concrete - Zhao, Juanjuan; Song, Xiaoyan; Shu, Xueyuan; Zhang, Huaying; Han, Liutao (Scientific Journal of Technology, 2026)
Slag-fly ash-metakaolin geopolymer concrete (GPC) uses industrial solid wastes (slag, fly ash) and natural minerals (metakaolin) as precursors, which undergo polycondensation reactions induced by alkali activators to form a zeolite-like aluminosilicate three-dimensional network structure. It not only has the advantages of low carbon and environmental protection, high strength, and good durability, but also shows excellent high-temperature resistance potential. It is a new type of green cementitious material that can replace traditional ordinary Portland cement (OPC) concrete and adapt to high-temperature environments and fire-resistant engineering scenarios. In recent years, scholars at home and abroad have carried out a large number of experimental studies and theoretical analyses on the high-temperature resistance performance of this ternary system GPC, and achieved rich research results. This paper systematically combs the research progress on the high-temperature resistance performance of slag-fly ash-metakaolin geopolymer concrete at home and abroad, focusing on the evolution of the material's macro-mechanical properties, the mechanism of microstructural deterioration, the key influencing factors and the modification and optimization paths under high-temperature action. It also detailedly compares the performance differences between it and OPC concrete in high-temperature environments, deeply analyzes the bottlenecks and technical difficulties existing in the current research work, and looks forward to the future research directions combined with the existing research status. The purpose is to provide comprehensive theoretical support and practical technical reference for the popularization and application of slag-fly ash-metakaolin geopolymer concrete in high-temperature engineering and fire-resistant structures.